The 'Migrant Crisis in the Mediterranean' as a Threat to Women's Security in the EU? A Contrapuntal Reading. Issue 3 (27th May 2022) - Bilgin, Pinar
ABSTRACT: The decentring agenda in European Studies has called for turning our gaze from the 'centre' towards the 'periphery'. This essay offers one decentred approach to EU migration governance in the Mediterranean: Studying geopolitical encounters between the receiving and sending spaces as constitutive of the very issues that are otherwise portrayed as autonomously developed. I will do this by adopting Edward Said's method of contrapuntal reading, which involves 'thinking through and interpreting together' narratives from different parts of the world towards recovering 'intertwined and overlapping histories' of humankind. The specific case I look at is the 2015 'migrant crisis in the Mediterranean' and the ways in which women's insecurities were portrayed. While such representations presume women's insecurities to have developed in the South/east and arrived in the North/west via migration, a contrapuntal reading of Fatima Mernissi's writings together with everyday portrayals of the 'crisis' points to the connectedness of otherwise differentiated experiences. What is represented as 'before Europe' (in Bernard McGrane's felicitous turn of phrase) is, at the same time, the 'aftermath of Europe' insofar as geopolitical encounters between North/west and South/east of the Mediterranean have been constitutive of women's insecurities.